2017
DOI: 10.1016/j.cgh.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Gas Volume Measured by Computerized Tomography Identifies Evacuation Disorders in Patients With Constipation

Abstract: Background & Aims Approximately one-third of patients who present with constipation to gastroenterology care have rectal evacuation disorders. We aimed to compare rectal gas volume, measured by computerized tomography (CT), in constipated patients with and without rectal evacuation disorders. Method In a retrospective study, we collected data from 1553 patients with constipation, evaluated over 20 years. We analyzed data from 141 patients evaluated by anorectal manometry, balloon expulsion tests, and colon t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 37 publications
1
25
1
Order By: Relevance
“…Our study shows that an RGV of 20 or 30 mL and an MRGTA of 10 cm 2 have PPVs of ≥75% at ~90% specificity for RED in constipated patients. These data complement our previous study, as we have identified the cut‐off values that have high specificity and PPV to select patients with likelihood to suffer RED and, therefore, to pursue other physiologic studies to confirm RED.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our study shows that an RGV of 20 or 30 mL and an MRGTA of 10 cm 2 have PPVs of ≥75% at ~90% specificity for RED in constipated patients. These data complement our previous study, as we have identified the cut‐off values that have high specificity and PPV to select patients with likelihood to suffer RED and, therefore, to pursue other physiologic studies to confirm RED.…”
Section: Discussionsupporting
confidence: 82%
“…In the future, we plan to perform prospective validation of RGV for screening of RED. As our prior study demonstrated validity of rectal area on the scout film of the CT scan to differentiate RED from non‐RED constipation and the current analysis shows the rectal gas area of 9 cm 2 may indicate RED, we recommend prospective validation of plain abdominal and/or pelvic radiograph instead of abdominopelvic CT, given the radiation exposure and cost of abdominopelvic CT . Given the lack of standardization of BET methodology and variable sensitivity and specificity of that test, we anticipate that, with further prospective validation, the measurement of rectal gas area on a plain abdominal and/or pelvic radiograph will become a useful screening test for RED in patients with constipation.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…A recent study demonstrated that the rectal gas volume, determined by abdominal computed tomography imaging, was greater in patients with a rectal evacuation disorder than in those without it, although the criterion of this study was not rectal evacuation disorders but chronic constipation. Other studies have shown that rectal evacuation disorders are the most common cause of refractory chronic constipation .…”
Section: Discussioncontrasting
confidence: 54%